Bioactive Whey Protein Concentrate and Lactose Stimulate Gut Function in Formula-fed Preterm Pigs. Issue 1 (January 2018) - Li, Yanqi; Nguyen, Duc Ninh; Obelitz-Ryom, Karina; Andersen, Anders D.; Thymann, Thomas; Chatterton, Dereck E.W.; Purup, Stig; Heckmann, Anne B.; Bering, Stine B.; Sangild, Per T.
ABSTRACT: Objective: Formula feeding is associated with compromised intestinal health in preterm neonates compared with maternal milk, but the mechanisms behind this are unclear. We hypothesized that the use of maltodextrin and whey protein concentrates (WPCs) with reduced bioactivity owing to thermal processing are important factors. Method: Ninety-two cesarean-delivered preterm pigs were fed increasing doses of formulas for 5 days (24–120 mL · kg −1 · day −1 ). In experiment 1, 4 groups of pigs (n = 15–16) were fed lactose- or maltodextrin-dominant formulas (lactose/maltodextrin ratios 3:1 or 1:3, respectively), containing WPC with either high or low levels of IgG (WPC1 or WPC2, respectively). In experiment 2, 2 groups of pigs (n = 15–16) were fed lactose-dominant formulas with either a bioactive WPC (BioWPC, produced by reduced thermal-processing) or a conventional WPC (ConWPC). Results: In experiment 1, pigs fed formula with WPC1 had higher villi, hexose absorption, and lactase activity in small intestine, relative to WPC2, but predominantly with the lactose-dominant formula (all P < 0.05). In experiment 2, the BioWPC product had higher bioactivity, as indicated by higher IgG, lactoferrin, and TGF-β2 levels, and better enterocyte proliferation in vitro. Pigs fed the BioWPC formula showed better feeding tolerance and higher intestinal villi and lactase activity (all P < 0.05). The BioWPC formula-fed pigs also had greater physical activity ( P < 0.05 on day 4) and tended to show improved hexose absorption and decreased gut permeability (both P ⩽ 0.09). Conclusions: Infant formulas containing lactose as the main carbohydrate, and WPC with reduced thermal processing, may support gut maturation and health in sensitive, preterm neonates. Abstract : Supplemental Digital Content is available in the text